IMPLEMENTASI STANDAR PENILAIAN DALAM PEMBELAJARAN EKONOMI DI SMA NEGERI 4 PAGARALAM - Chatida Noor Ardilla; Siti Fatimah; Deskoni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
This study discusses the implementation of the economic assessment standards in learning in SMAN 4 Pagaralam. The formulation of the problem is how the implementation of the economic assessment standards in learning in SMAN 4 Pagaralam? The variables of this study is the economic assessment standards in learning. This research uses descriptive method. The subjects were 4 economics teacher at SMAN 4 Pagaralam. Data were collected by interview and documentation. The results show that the assessment standards are 8 aspects that make the design and assessment criteria and are informed at the beginning of the semester is very good with the average percentage of 100%, developing indicators and determining the valuation technique is very good with the average percentage of 87.5%, developing assessment instruments and guidelines for good with the acquisition of a percentage of 56.25%, carrying out tests, observations, assignments, and other necessary forms well with the average percentage of 58.33%, processing the results of the assessment of learners well with the average percentage of 75%, restoring the examination results of students work very well with a mean percentage of 100%, utilizing the results of the assessment for learning improvement both with a mean percentage of 75%. reported the results of the assessment included in the criteria very well with the acquisition of a percentage of 100%. Economics teacher suggested that more focus in preparing all the completeness of assessment and assessment techniques to be used to achieve the indicators that have been set.